1997
DOI: 10.1046/j.1365-2435.1997.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy allocation in polymorphic Brown Trout

Abstract: 1. To evaluate differences in energy allocation to gonadal development of resident and anadromous Brown Trout, Salmo trutta, we analysed tissue composition and energy contents of adults of the two morphs from three small streams in southernmost Norway. Somatic energy per unit mass of anadromous spawners (5·0 ± 0·6 kJ g–1 wet weight) was 1·1 times that of the residents. This difference was chiefly due to a 1·4 ‐times higher lipid content in anadromous (4·9 ± 1·5%) than resident trout. The somatic protein and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 47 publications
6
62
1
1
Order By: Relevance
“…Lipid content of brown trout egg in the present study was 9.3%, in accordance with wild lake trout egg (9.1-9.9%) from Lake Michigan (Czesny et al, 2012) and it was slightly higher than wild brown trout egg (7.8-8.6%) from some Norwegian streams (Jonsson and Jonsson, 1997). The latter study reported that the energetic investment in gonads to relative soma in female brown trout during the maturation was estimated at 67%.…”
Section: Discussionsupporting
confidence: 86%
“…Lipid content of brown trout egg in the present study was 9.3%, in accordance with wild lake trout egg (9.1-9.9%) from Lake Michigan (Czesny et al, 2012) and it was slightly higher than wild brown trout egg (7.8-8.6%) from some Norwegian streams (Jonsson and Jonsson, 1997). The latter study reported that the energetic investment in gonads to relative soma in female brown trout during the maturation was estimated at 67%.…”
Section: Discussionsupporting
confidence: 86%
“…It is well established that maintaining ovarian tissue is energetically expensive whereas maintaining testicular tissue is relatively inexpensive (Hayward and Gillooly, 2011;Jonsson and Jonsson, 1997;Yong and Grober, 2013; but see Olsson et al, 1997). Maintaining ovarian tissue has negative impacts on individual survival, growth, immunocompetence and future reproductive efforts (Bergeron et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…Predators can intercept male courtship signals (Taylor and Ryan, 2013) and competing aggressively to acquire mating opportunities can be energetically costly and carry high risks of injury (Brick and Jakobsson, 2002;Neat et al, 1998). Females accrue costs by supporting energetically expensive ovarian tissues Hayward and Gillooly, 2011;Jonsson and Jonsson, 1997;Yong and Grober, 2013). To sustain current reproductive efforts, females may allocate energy away from somatic growth, fat storage or future reproduction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional condition may be suppressed for a considerable period after the reproductive season. The greater onus is likely to be on females (Craig 1977, Jonsson andJonsson 1997).…”
Section: Discussionmentioning
confidence: 99%